Ventilation of the stone - Cress, Fannie Jane (My University, 1894)
Introduction: The question of ventilation although an old one, must be constantly bought to our minds or we grow careless and do not give it the attention it deserves. It is also a question, the principles of which are not well understood by the majority of people. In order that we may do our part to remedy a large amount of the injury which is done by living in ill-ventilated homes, either through ignorance of the laws of health or carelessness, it is necessary for us to study the conditions under which thorough ventilation is secured. One of the most important things to be considered, is the air and its composition. The earth is surrounded by a covering from fifty to five hundred miles in depth, which we call the atmosphere. This consists of the air which becomes rarer and rarer as we ascend and less able to support life. The chief constituents of the air when pure, are oxygen and nitrogen, found in the proportion, by weight, of seventy-seven parts of nitrogen and twenty-three parts of oxygen in every hundred parts air and, by volume, of four parts of nitrogen to one part of oxygen. Besides these, the air contains small quantities of water in the form of vapor; ammonia; three parts in ten thousand parts of air; the same amount of carbon dioxide; one part of ozone in seven hundred thousand parts of air; and nitrous and nitric compounds.
Citation: Cress, Fannie Jane. Ventilation of the stone. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Air; Atmosphere; Ventilation; Stone; Global; Earth science; Theses; Manuscripts (documents)